ANALISIS KANDUNGAN LOGAM TIMBAL (Pb) DAN LAJU KONSUMSI AMAN KERANG KEPAH (Polymesoda erosa) DI SUNGAI DONAN CILACAP - Amazonia Dhita Risanti; Suratman Suratman; Agnes Fitria Widiyanto (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2013)
ABSTRACT One of the content that contained in Donan River is known as a lead (Pb). Lead that contained in the water will accumulate in the body of water organisme, one of which is the body shells (Polymesoda erosa). This type of research is a descriptive study and use the test